The Relationship Between 7th and 8th Grade Boys’ and Girls’ and Their Parents’ Motivational Beliefs About Mathematics - Baranauskaitė, Emilė; Butkienė, Dovilė (Pedagogika, 2023)
According to the EVT Parent Socialization Model (Wigfield et al., 2006), students’ motivational beliefs are influenced by their parents’ beliefs, which often reflect parents’ gender stereotypes. The aim of the present study was to compare girls’ and boys’ beliefs in grades 7–8 and their parents’ beliefs about mathematical abilities and mathematics values and evaluate the associations between these beliefs. The participants in this study were 76 students in grades 7–8 (47 boys and 29 girls), as well as 76 of their mothers. Students’ motivational beliefs were measured with the Mathematical Ability and Value Beliefs Questionnaire. Perceived parents’ beliefs and actual parents’ beliefs were measured with the Student-Perceived Parents’ Beliefs / Parents’ Beliefs about Mathematical Ability and Mathematics Values Questionnaire. Students’ grades for the first semester (trimester) of the 2020–21 academic year were used as a measure of students’ math performance. The findings indicated that girls had more negative ability beliefs and values about mathematics than did boys, despite the fact that their math performance was the same. Compared to boys, girls also thought that their parents rated their mathematical abilities lower. However, actual parents’ beliefs about students’ mathematical abilities and mathematical values did not differ by child’s gender. It was also found that children’s motivational beliefs were associated with perceived parents’ and parents’ own motivational beliefs about mathematics.